DEEP- SEA BACTERIA AND THEIR BIOTECHNOLOGICAL POTENTIALS - Ocky Karna radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Deep-sea environment characterized by its low temperature, high hydrostatic pressure, limited nutrient contents, and constant darkness has been a hostile environment for most marine microorganisms. Therefore it is a home for low temperature and high pressure-loving bacteria believed to functionally over shallow water intruders. Deep-sea has been regarded as rainforests in terms of their microbial diversity. Thus, the deep-sea should commend itself to microbiologists and biotechnologists alike as source of novel microorganisms and exploitable properties. Near Indonesia several deep-sea trenches exist with diverse environmental conditions. However, up to now there has been no effort to study the microbial communities of those deep-sea environments by Indonesian scientists. This is mainly because of the lack of knowledge in the field of deep-sea microbiology in Indonesia.